2016
DOI: 10.31235/osf.io/286er
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The GSA Difference: LGBTQ and Ally Experiences in High Schools with and without Gay-Straight Alliances

Abstract: Abstract:We examine the lived experiences of high-school students who participated in lesbian, gay, bisexual, transgender, and queer (LGBTQ)-centered activism of some kind, highlighting the promise of gay-straight alliance groups by comparing the experiences of students at schools with gay-straight alliances (GSA schools) with the experiences of students at schools that did not have an LGBTQ-specific group (no-GSA schools). We compare students at GSA and no-GSA schools based on their experiences of harassment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…For example, one study showed that characteristics of GSAs are predictive of school engagement for LGBTQ students, including GSA size, visibility, activity, and the level of support for the GSA among people at school (Seelman, Forge, Walls, & Bridges, 2015). Fetner and Elafros (2015) interviewed U.S. and Canadian young adults about their memories of high school and the role that having a GSA played in their life; participants reported diverse experiences regarding participation in GSAs and described notable differences in the presence of supportive adults in GSAs, as well as differences in other school policies relevant to LGBTQ inclusion and school safety. The influence of GSAs on psychological well-being may be related less to generic participation and more to the quality and amount of time spent in GSA activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study showed that characteristics of GSAs are predictive of school engagement for LGBTQ students, including GSA size, visibility, activity, and the level of support for the GSA among people at school (Seelman, Forge, Walls, & Bridges, 2015). Fetner and Elafros (2015) interviewed U.S. and Canadian young adults about their memories of high school and the role that having a GSA played in their life; participants reported diverse experiences regarding participation in GSAs and described notable differences in the presence of supportive adults in GSAs, as well as differences in other school policies relevant to LGBTQ inclusion and school safety. The influence of GSAs on psychological well-being may be related less to generic participation and more to the quality and amount of time spent in GSA activities.…”
Section: Discussionmentioning
confidence: 99%
“…In a focus group study of 31 LGBT youth attending public high schools, youth consistently named GSAs as a strategy for preventing school violence (Grossman, Haney, Edwards, Alessi, Ardon, & Howell, 2009). The presence of a GSA has also been associated with a greater reported likelihood that school personnel will intervene when they hear homophobic remarks (Kosciw et al, 2014), greater support from teachers and administrators for sexual minority students, more friendships across sexual identities (Fetner & Elafros, 2015), less absenteeism (Poteat et al, 2013), more school belonging (Heck, Flentje, & Cochran, 2011), and higher grade point average for students who score high on school engagement (Seelman, Walls, Hazel, & Wisneski, 2012). In addition to the length of time the GSA had been established, Seelman and colleagues (2015) found that other GSA characteristics may be consequential.…”
Section: Gsas: Experiences At Schoolmentioning
confidence: 99%
“…School‐sponsored programs such as Gay‐Straight Alliances (GSAs; also known as Gender and Sexuality Alliances) and school policies focused on support for LGBTQ students (LGBTQ‐focused policies) have also been identified as effective means for improving school climates, especially for LGBTQ youth (Chesir‐Teran & Hughes, ; Fetner & Elafros, ; Goodenow et al., ; Heck, Flentje, & Cochran, ; Kosciw, Greytak, Giga, Villenas, & Danischewski, ; Marx & Kettrey, ; McGuire, Anderson, Toomey, & Russell, ). Enumerated antibullying policies that are inclusive of sexual orientation and gender identity are associated with stronger feelings of safety, less victimization (Kosciw et al., ; O'Shaughnessy, Russell, Heck, Calhoun, & Laub, ), and lower rates of suicidal behavior among LGB youth (Hatzenbuehler & Keyes, ).…”
Section: Bias‐based Bullying In Schoolsmentioning
confidence: 99%
“…Youth in schools with GSAs engage in less risky behaviors related to alcohol, tobacco, and sex, and are less likely to be truant (Poteat, Sinclair, DiGiovanni, Koenig, & Russell, ). LGBTQ youth in schools with a GSA also report more support from classmates, teachers, and administrators (Fetner & Elafros, ; Kosciw et al., ). Notably, with the exception of a few recent studies (Fetner & Elafros, ; Poteat, Calzo, & Yoshikawa, ; Poteat, Heck, Yoshikawa, & Calzo, ), most studies of GSAs do not distinguish between sexual orientation and gender identity.…”
Section: Bias‐based Bullying In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation